Model Laboratorium Pola Aliran Pada Krib Impermeable Terhadap Variasi Debit Dan Posisi Krib Di Sungai Berbelok - Hasibuan, Bangun Sugito Riski; Mudjiatko, Mudjiatko; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Crib is building cross river that serves as building steering flow to protect riverbanks from attacks the current flows. Model laboratory used to demonstrate the phenomenon of pattern flows that occur around the crib at the maender. Crib models used in this study is crib type impermeable with dimensions of length 0.15 m, width 0.03 m and high 0.15 m. The flow rate used is 0.00134 m3 / sec (Q1), 0.00298 m3 / sec (Q2) and 0.0056 m3 / sec (Q3). Position crib used is 0 ° (S1), 15 ° (S2) and 30 ° (S3) to turn the corner. Distance between crib is 30 cm and the configuration crib angle of 135 ° tothe wall outside of the turn. The pattern flows at each position variation crib with debit Q1, vortex flow occurs in the space between the crib and crib with a radius lengthy of the vortexis relatively short. The pattern flows at each position variation crib with debit Q2, vortex flow occurs around the crib witha radius lengthy of the vortex is relatively modest. The pattern flows at each position variation crib with debit Q3, vortex flow occurs before at the crib, a space between the crib and crib with a radius lengthy of the vortexrelatively long. Overall,phenomenon the pattern flow of the most well occur indebit Q1 position crib S2.Keywords: patterns of flow, maender, crib type of impermeable